Fingolimod effects on the brain are mediated through biochemical modulation of bioenergetics, autophagy, and neuroinflammatory networks. Issue 19 (8th August 2022) - Mirzaei, Mehdi; Abyadeh, Morteza; Turner, Anita J.; Wall, Roshana Vander; Chick, Joel M.; Paulo, Joao A.; Gupta, Veer K.; Basavarajappa, Devaraj; Chitranshi, Nitin; Mirshahvaladi, Seyed Shahab Oddin; You, Yuyi; Fitzhenry, Matthew J.; et al.
Abstract: Fingolimod (FTY720) is an oral drug approved by the Food and Drug Administration (FDA) for management of multiple sclerosis (MS) symptoms, which has also shown beneficial effects against Alzheimer's (AD) and Parkinson's (PD) diseases pathologies. Although an extensive effort has been made to identify mechanisms underpinning its therapeutic effects, much remains unknown. Here, we investigated Fingolimod induced proteome changes in the cerebellum (CB) and frontal cortex (FC) regions of the brain which are known to be severely affected in MS, using a tandem mass tag (TMT) isobaric labeling‐based quantitative mass‐spectrometric approach to investigate the mechanism of action of Fingolimod. This study identified 6749 and 6319 proteins in CB and FC, respectively, and returned 2609 and 3086 differentially expressed proteins in mouse CB and FC, respectively, between Fingolimod treated and control groups. Subsequent bioinformatics analyses indicated a metabolic reprogramming in both brain regions of the Fingolimod treated group, where oxidative phosphorylation was upregulated while glycolysis and pentose phosphate pathway were downregulated. In addition, modulation of neuroinflammation in the Fingolimod treated group was indicated by upregulation of retrograde endocannabinoid signaling and autophagy pathways, and downregulation of neuroinflammation related pathways including neutrophil degranulation and the IL‐12 mediated signaling pathway. Our findings suggest that Fingolimod may exert its protective effects on the brain by inducing metabolic reprogramming and neuroinflammation pathway modulation.